Nanofiber aerogel with PAN as matrix and preparation method and application of nanofiber aerogel
Through the preparation of PAN/SiO2 nanofiber aerogel, the contradiction between the mechanical properties and high temperature resistance of traditional aerogel materials is solved, and the characteristics of excellent thermal insulation performance, high mechanical strength and ultra-light are achieved, and the insulation and heat insulation are expanded The application range of materials and reduces the production cost.
Patent Information
- Application Number
- CN202411691351.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-07
AI Technical Summary
There is a contradiction between the mechanical properties and high temperature resistance of traditional aerogel materials, and it is difficult to be widely used in thermal insulation applications in aerospace, construction and other fields.
The preparation method of PAN/SiO2 nanofiber aerogel is adopted, and the C/SiO2 nanofiber aerogel with excellent thermal insulation properties and mechanical strength is formed through electrospinning and physical cross-linking technology.
It achieves excellent thermal insulation performance, high mechanical strength and ultra-light, can maintain shape under large pressure, expands the application range of insulation materials, and reduces the preparation cost.
Smart Images

Figure CN119264512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiber aerogel, and in particular to a nanofiber aerogel with PAN as a matrix, and a preparation method and application thereof. Background Art
[0002] Aerogel has a wide range of potential applications in thermal insulation in aerospace, building roofs / wall panels, automotive industry, packaging and transportation, etc. due to its ultra-high porosity, large specific surface area, extremely low density and thermal conductivity. Traditional aerogels are divided into two categories: one is organic polymer aerogel materials, such as cellulose aerogel, chitosan aerogel, starch aerogel, etc., which have certain mechanical properties but poor high temperature resistance; the other is inorganic aerogel materials, such as silicon aerogel, carbon aerogel, metal oxide aerogel, etc., which often have good high temperature resistance, but poor mechanical properties have always been the main factor restricting their wide application. Taking SiO2 aerogel as an example, SiO2 aerogel is gradually improved from the initial three-dimensional stacking of nanoparticles to SiO2 nanofibers replacing nanoparticles, thereby improving the brittleness of SiO2 aerogel to a certain extent, making SiO2 aerogel have certain compressibility, but SiO2 aerogel still has poor tensile resistance.
[0003] Therefore, the research results show that a PAN-based C / SiO2 nanofiber aerogel with excellent thermal insulation performance and high mechanical strength is of great value. Summary of the invention
[0004] The purpose of the present invention is to provide a nanofiber aerogel with PAN as a matrix and a preparation method and application thereof in order to overcome the deficiencies of the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing PAN / SiO2 nanofiber aerogel, comprising the following steps:
[0007] 1) mixing tetraethyl silicate and a solvent and evaporating the mixture to obtain a spinning solution, and electrospinning the spinning solution to obtain a SiO2 nanofiber membrane;
[0008] 2) stirring and mixing SiO2 nanofiber membrane, polyacrylonitrile and N,N-dimethylformamide to obtain physically cross-linked PAN / SiO2 nanofiber colloid;
[0009] 3) The PAN / SiO2 nanofiber colloid is immersed in water and then sequentially frozen and freeze-dried to obtain a PAN / SiO2 nanofiber aerogel.
[0010] Preferably, in step 1), the volume ratio of tetraethyl silicate to solvent is 1:0.6-1.1, the solvent is a mixture of anhydrous ethanol, water and hydrochloric acid, the volume ratio of anhydrous ethanol, water and hydrochloric acid is 95-115:30-45:1, and the mass concentration of hydrochloric acid is 5-15%.
[0011] Preferably, the evaporation temperature in step 1) is 78-85°C, the time is 35-100 min, and the evaporation is carried out under stirring at a stirring rate of 150-450 r / min;
[0012] During the electrostatic spinning process, the voltage is 15-30 kV, the temperature is 20-30° C., the relative humidity is 30-40%, and the distance between the spinning needle and the receiving roller is 10-25 cm.
[0013] Preferably, in step 2), the mass volume ratio of the SiO2 nanofiber membrane and N,N-dimethylformamide is 1g:35-50mL, and the mass volume ratio of polyacrylonitrile and N,N-dimethylformamide is 1g:30-60mL; the stirring and mixing time is 50-150min, and the rotation speed is 1600-2200r / min.
[0014] Preferably, in step 3), the soaking time is 72 to 120 hours, the water is replaced during the soaking period, and the number of water replacements is 10 to 20 times; the freezing temperature is -75 to -18°C, and the time is 12 to 36 hours; the freeze-drying pressure is 2 to 10 Pa, the temperature is -80 to -40°C, and the time is 65 to 110 hours.
[0015] The present invention also provides the PAN / SiO2 nanofiber aerogel prepared by the preparation method of the PAN / SiO2 nanofiber aerogel.
[0016] The present invention also provides a method for preparing C / SiO2 nanofiber aerogel from the PAN / SiO2 nanofiber aerogel, comprising the following steps:
[0017] The PAN / SiO2 nanofiber aerogel is pre-oxidized and carbonized in sequence to obtain C / SiO2 nanofiber aerogel.
[0018] Preferably, the pre-oxidation temperature is 240-300°C, the time is 100-160 min, and the heating rate to the pre-oxidation temperature is 1-3°C / min;
[0019] The carbonization temperature is 700-900° C., the time is 20-80 min, the heating rate to the carbonization temperature is 2-5° C. / min, and the carbonization is carried out under a nitrogen atmosphere.
[0020] The present invention also provides C / SiO2 nanofiber aerogel prepared by the method for preparing C / SiO2 nanofiber aerogel using the PAN / SiO2 nanofiber aerogel.
[0021] The present invention also provides application of the PAN / SiO2 nanofiber aerogel or the C / SiO2 nanofiber aerogel in thermal insulation materials.
[0022] The beneficial effects of the present invention include the following:
[0023] 1) The C / SiO2 nanofiber aerogel prepared with PAN as the matrix of the present invention can achieve the characteristics of good thermal insulation performance, high mechanical strength and ultra-lightness. The C / SiO2 nanofiber aerogel with a thickness of 1.5 cm and a diameter of 3 cm can withstand a weight of more than 5 kg without obvious deformation. At the same time, the strength can reach more than 170 kPa under the condition of 10% deformation. The PAN / SiO2 nanofiber aerogel with a thickness of 2 cm and a diameter of 3.6 cm does not produce obvious deformation when subjected to a pressure of more than 5 kg. The nanofiber aerogel of the present invention exhibits good mechanical properties, which can meet the requirements of thermal insulation materials for support and ultra-lightness, and further expand the application scope of C / SiO2 nanofiber aerogel and PAN / SiO2 nanofiber aerogel in thermal insulation materials.
[0024] 2) The PAN / SiO2 nanofiber aerogel and C / SiO2 nanofiber aerogel prepared with PAN as the matrix in the present invention greatly improve the mechanical strength of traditional SiO2 nanofiber aerogel, and provide a new idea for the preparation of new thermal insulation materials; the process for preparing nanofiber aerogel in the present invention is relatively simple, the reaction conditions are mild, no large equipment is required, and the cost is saved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The process flow chart of preparing C / SiO2 nanofiber aerogel of the present invention;
[0026] Figure 2 This is a picture of the C / SiO2 nanofiber aerogel prepared in Example 1;
[0027] Figure 3 This is a picture of the PAN / SiO2 nanofiber aerogel prepared in Example 4;
[0028] Figure 4 This is a test diagram of the compressive strength of the C / SiO2 nanofiber aerogel prepared in Example 1;
[0029] Figure 5 This is a compressive strength test diagram of the C / SiO2 nanofiber aerogel prepared in Example 2. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing PAN / SiO2 nanofiber aerogel, comprising the following steps:
[0031] 1) mixing tetraethyl silicate and a solvent and evaporating the mixture to obtain a spinning solution, and electrospinning the spinning solution to obtain a SiO2 nanofiber membrane;
[0032] 2) stirring and mixing SiO2 nanofiber membrane, polyacrylonitrile and N,N-dimethylformamide to obtain physically cross-linked PAN / SiO2 nanofiber colloid;
[0033] 3) The PAN / SiO2 nanofiber colloid is immersed in water and then sequentially frozen and freeze-dried to obtain a PAN / SiO2 nanofiber aerogel.
[0034] In the present invention, the volume ratio of tetraethyl silicate to solvent in step 1) is preferably 1:0.6-1.1, more preferably 1:0.7-1.0, and more preferably 1:0.8-0.9. The solvent is preferably a mixture of anhydrous ethanol, water and hydrochloric acid. The volume ratio of anhydrous ethanol, water and hydrochloric acid is preferably 95-115:30-45:1, more preferably 100-110:33-42:1, and more preferably 102.35-105:35-38.65:1. The mass concentration of hydrochloric acid is preferably 5-15%, more preferably 8-12%, and more preferably 10%.
[0035] In the present invention, the evaporation temperature in step 1) is preferably 78-85°C, more preferably 80-83°C, more preferably 81-82°C, and the evaporation time is preferably 35-100 min, more preferably 40-80 min, more preferably 55-65 min; the evaporation is preferably carried out under stirring conditions, and the stirring rate is preferably 150-450 r / min, more preferably 250-400 r / min, more preferably 300-350 r / min.
[0036] In the present invention, during the electrospinning process described in step 1), the voltage is preferably 15 to 30 kV, more preferably 18 to 25 kV, more preferably 20 to 22 kV, the temperature is preferably 20 to 30 ° C, more preferably 22 to 28 ° C, more preferably 24 to 25 ° C, the relative humidity is preferably 30 to 40%, more preferably 32 to 38%, more preferably 34 to 35%, and the distance (vertical distance) between the spinning needle and the receiving roller is preferably 10 to 25 cm, more preferably 15 to 20 cm, and more preferably 18 cm.
[0037] In the electrospinning process of the present invention, the rotation speed of the receiving drum is preferably 80-150 r / min, more preferably 90-130 r / min, and more preferably 100-110 r / min; the spinneret hole translation speed (needle translation speed) is preferably 200-350 mm / min, more preferably 250-320 mm / min, and more preferably 280-300 mm / min; the translation stroke is preferably 450-550 mm, more preferably 480-520 mm, and more preferably 500 mm.
[0038] In the present invention, electrospinning is preferably carried out using a syringe; the specification of the syringe is preferably 5-20 mL, more preferably 10-15 mL; the inner diameter of the syringe needle is preferably 0.39-0.43 mm, more preferably 0.41-0.42 mm; the outer diameter of the syringe needle is preferably 0.69-0.73 mm, more preferably 0.71-0.72 mm.
[0039] In the present invention, the mass volume ratio of the SiO2 nanofiber membrane and N,N-dimethylformamide (DMF) in step 2) is preferably 1g:35-50mL, further preferably 1g:38-45mL, more preferably 1g:40-43mL, the mass volume ratio of polyacrylonitrile (PAN) and N,N-dimethylformamide is preferably 1g:30-60mL, further preferably 1g:35-55mL, more preferably 1g:40-45mL; the stirring and mixing time is preferably 50-150min, further preferably 70-120min, more preferably 80-100min, the rotation speed is preferably 1600-2200r / min, further preferably 1800-2100r / min, more preferably 1900-2000r / min.
[0040] In the present invention, the soaking time in step 3) is preferably 72 to 120 hours, more preferably 80 to 110 hours, and more preferably 90 to 100 hours. The water is replaced during the soaking period, and the number of water replacements is preferably 10 to 20 times, more preferably 13 to 17 times, and more preferably 15 times.
[0041] In the present invention, the freezing temperature in step 3) is preferably -75 to -18°C, more preferably -65 to -25°C, more preferably -55 to -35°C, and the time is preferably 12 to 36 hours, more preferably 15 to 30 hours, more preferably 20 to 25 hours; the freeze-drying pressure is preferably 2 to 10 Pa, more preferably 4 to 8 Pa, more preferably 5 to 6 Pa, the temperature is preferably -80 to -40°C, more preferably -70 to -50°C, more preferably -60°C, and the time is preferably 65 to 110 hours, more preferably 72 to 108 hours, more preferably 84 to 95 hours.
[0042] The present invention also provides the PAN / SiO2 nanofiber aerogel prepared by the preparation method of the PAN / SiO2 nanofiber aerogel.
[0043] The present invention also provides a method for preparing C / SiO2 nanofiber aerogel from the PAN / SiO2 nanofiber aerogel, comprising the following steps:
[0044] The PAN / SiO2 nanofiber aerogel is pre-oxidized and carbonized in sequence to obtain C / SiO2 nanofiber aerogel.
[0045] In the present invention, the pre-oxidation temperature is preferably 240-300°C, more preferably 260-280°C, more preferably 270°C, the time is preferably 100-160min, more preferably 120-150min, more preferably 130-140min, and the heating rate to the pre-oxidation temperature is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, more preferably 2°C / min.
[0046] In the present invention, the carbonization temperature is preferably 700-900°C, more preferably 750-850°C, more preferably 800-820°C, the time is preferably 20-80min, more preferably 30-60min, more preferably 40-50min, the heating rate to the carbonization temperature is preferably 2-5°C / min, more preferably 3-4°C / min, and the carbonization is preferably carried out under a nitrogen atmosphere.
[0047] In the present invention, the carbonization is preferably heated to 250-350°C at a heating rate of 3-5°C / min, and then heated to 700-900°C at a heating rate of 1-3°C / min, more preferably heated to 280-320°C at a heating rate of 3.5-4.5°C / min, and then heated to 750-850°C at a heating rate of 1.5-2.5°C / min, more preferably heated to 300°C at a heating rate of 4°C / min, and then heated to 800°C at a heating rate of 2°C / min.
[0048] The present invention also provides C / SiO2 nanofiber aerogel prepared by the method for preparing C / SiO2 nanofiber aerogel using the PAN / SiO2 nanofiber aerogel.
[0049] The present invention also provides application of the PAN / SiO2 nanofiber aerogel or the C / SiO2 nanofiber aerogel in thermal insulation materials.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] Example 1
[0052] 20 mL of tetraethyl silicate, 10.235 mL of anhydrous ethanol, 3.865 mL of ultrapure water and 0.1 mL of hydrochloric acid with a mass concentration of 10% were mixed, the mixture was stirred at a speed of 250 r / min, heated and evaporated at 82°C for 40 min to perform a hydrolysis reaction until the mass loss fraction of the spinning solution reached 58%. Then the spinning solution was cooled to room temperature, placed in a 15 mL syringe, and electrospinning was performed when the solution dripped at a rate of 1 to 2 drops per second to obtain a SiO2 nanofiber membrane.
[0053] The parameters for electrospinning of the spinning solution are as follows: the inner diameter of the syringe needle is 0.41 mm, the outer diameter of the needle is 0.71 mm, the voltage of the electrospinning is 20 kV, the receiving device is coated with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 15 cm, the rotation speed of the receiving roller is 100 r / min, the translation speed of the electrospinning needle is 300 mm / min, the translation stroke of the electrospinning is 500 mm, the spinning temperature is 22 ° C, and the relative humidity is 32%.
[0054] 1 g of SiO2 nanofiber membrane was cut into pieces and added into 40 mL of DMF. The mixture was stirred at 1800 r / min for 1 h under a cantilever high-speed electric stirrer. During the stirring process, 1 g of PAN was added and the mixture was stirred at 2000 r / min for 20 min to form a uniform physically cross-linked PAN / SiO2 nanofiber colloid.
[0055] The PAN / SiO2 nanofiber colloid was added to ultrapure water and soaked for 90 hours. The water was changed 15 times during the soaking period. The intervals between changing the water were the same. After the soaking, the colloid showed a certain shape to obtain PAN / SiO2 gel. The PAN / SiO2 gel with a certain shape was placed in a vacuum freeze dryer, frozen at -55°C for 12 hours, and then freeze-dried at -60°C and 5Pa for 84 hours to obtain PAN / SiO2 nanofiber aerogel.
[0056] The PAN / SiO2 nanofiber aerogel was placed in a muffle furnace for pre-oxidation under air atmosphere, heated to 280°C at a heating rate of 1°C / min, and kept warm for 120 min; it was carbonized in a tubular furnace under nitrogen atmosphere, heated from 20°C to 300°C at a heating rate of 5°C / min, and then heated from 300°C to 850°C at a heating rate of 2°C / min, and kept warm for 30 min to obtain C / SiO2 nanofiber aerogel.
[0057] The C / SiO2 nanofiber aerogel prepared with PAN as the matrix in this embodiment can achieve the characteristics of high temperature resistance, high mechanical strength and ultra-lightness. The C / SiO2 nanofiber aerogel with a thickness of 1.5 cm and a diameter of 3 cm can withstand a weight of more than 5 kg without obvious deformation. The strength can reach 170 kPa under the condition of 10% deformation, showing good mechanical properties. At the same time, the mass of the C / SiO2 nanofiber aerogel is measured to be only 0.904 g, which can meet the requirements of thermal insulation materials for support and ultra-lightness.
[0058] Example 2
[0059] 40 mL of tetraethyl silicate, 20.48 mL of anhydrous ethanol, 7.75 mL of ultrapure water and 0.2 mL of hydrochloric acid with a mass concentration of 10% were mixed, the mixture was stirred at a speed of 250 r / min, heated and evaporated at 82°C for 60 min to perform a hydrolysis reaction until the mass loss fraction of the spinning solution reached 58%. Then the spinning solution was cooled to room temperature, placed in a 20 mL syringe, and electrostatic spinning was performed when the solution dripped at a speed of 1 to 2 drops per second to obtain a SiO2 nanofiber membrane.
[0060] The parameters for electrospinning of the spinning solution are as follows: the inner diameter of the syringe needle is 0.41 mm, the outer diameter of the needle is 0.71 mm, the voltage of the electrospinning is 20 kV, the receiving device is coated with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 15 cm, the rotation speed of the receiving roller is 100 r / min, the translation speed of the electrospinning needle is 300 mm / min, the translation stroke of the electrospinning is 500 mm, the spinning temperature is 23 ° C, and the relative humidity is 32%.
[0061] 2 g of SiO2 nanofiber membrane was cut into pieces and added into 85 mL of DMF. The mixture was stirred and mixed at 1800 r / min for 1 h under a cantilever high-speed electric stirrer. During the stirring process, 1.8 g of PAN was added and the mixture was stirred and mixed at 2000 r / min for 20 min to form a uniform physically cross-linked PAN / SiO2 nanofiber colloid.
[0062] The PAN / SiO2 nanofiber colloid was added to ultrapure water and soaked for 120 hours. The water was changed 17 times during the soaking period. The intervals between water changes were the same. After the soaking, the colloid showed a certain shape to obtain PAN / SiO2 gel. The PAN / SiO2 gel with a certain shape was placed in a vacuum freeze dryer, frozen at -35°C for 30 hours, and then freeze-dried at -50°C and 5Pa for 108 hours to obtain PAN / SiO2 nanofiber aerogel.
[0063] The PAN / SiO2 nanofiber aerogel was placed in a muffle furnace for pre-oxidation under air atmosphere, heated to 260°C at a heating rate of 1°C / min, and kept warm for 150 minutes; it was carbonized in a tubular furnace under nitrogen atmosphere, heated from 20°C to 300°C at a heating rate of 5°C / min, and then heated from 300°C to 800°C at a heating rate of 2°C / min, and kept warm for 60 minutes to obtain C / SiO2 nanofiber aerogel.
[0064] The C / SiO2 nanofiber aerogel prepared with PAN as the matrix in this embodiment can achieve the characteristics of high mechanical strength and ultra-lightness. The C / SiO2 nanofiber aerogel with a thickness of 2 cm and a diameter of 3 cm can withstand a weight of more than 5 kg without obvious deformation. Under the condition of 10% deformation, the strength can reach 170 kPa, showing good mechanical properties, which can meet the requirements of thermal insulation materials for support and ultra-lightness.
[0065] Example 3
[0066] 20mL of tetraethyl silicate, 11.2mL of anhydrous ethanol, 4mL of ultrapure water and 0.1mL of hydrochloric acid with a mass concentration of 12% were mixed, the mixed solution was stirred at a speed of 350r / min, heated and evaporated at 80°C for 80min to perform a hydrolysis reaction until the mass loss fraction of the spinning solution reached 60%. Then it was cooled to room temperature, the spinning solution was placed in a syringe with a specification of 12mL, and electrostatic spinning was performed when the solution dripped at a speed of 1 to 2 drops per second to obtain a SiO2 nanofiber membrane.
[0067] The parameters for electrospinning of the spinning solution are as follows: the inner diameter of the syringe needle is 0.42 mm, the outer diameter of the needle is 0.72 mm, the voltage of the electrospinning is 22 kV, the receiving device is coated with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 130 r / min, the translation speed of the electrospinning needle is 280 mm / min, the translation stroke of the electrospinning is 480 mm, the spinning temperature is 25 ° C, and the relative humidity is 35%.
[0068] 1 g of SiO2 nanofiber membrane was cut into pieces and added into 45 mL of DMF. The mixture was stirred and mixed at 1700 r / min for 1.2 h under a cantilever high-speed electric stirrer. During the stirring process, 1 g of PAN was added and the mixture was stirred and mixed at 2100 r / min for 25 min to form a uniform physically cross-linked PAN / SiO2 nanofiber colloid.
[0069] The PAN / SiO2 nanofiber colloid was added to ultrapure water and soaked for 100 hours. The water was changed 13 times during the soaking period. The intervals between water changes were the same. After the soaking, the colloid showed a certain shape to obtain PAN / SiO2 gel. The PAN / SiO2 gel with a certain shape was placed in a vacuum freeze dryer, frozen at -65°C for 20 hours, and then freeze-dried at -70°C and 5Pa for 72 hours to obtain PAN / SiO2 nanofiber aerogel.
[0070] The PAN / SiO2 nanofiber aerogel was placed in a muffle furnace for pre-oxidation under air atmosphere, and the temperature was increased to 270°C at a heating rate of 2°C / min and kept warm for 130 min; it was carbonized in a tubular furnace under nitrogen atmosphere, and the temperature was increased from 20°C to 280°C at a heating rate of 4°C / min, and then from 280°C to 780°C at a heating rate of 1.5°C / min, and kept warm for 50 min to obtain C / SiO2 nanofiber aerogel.
[0071] The C / SiO2 nanofiber aerogel prepared with PAN as the matrix in this embodiment can achieve the characteristics of high temperature resistance, high mechanical strength and ultra-lightness. The C / SiO2 nanofiber aerogel with a thickness of 1.5 cm and a diameter of 3 cm can withstand a weight of more than 5 kg without obvious deformation. Under the condition of 10% deformation, the strength can reach 175 KPa, showing good mechanical properties, which can meet the requirements of thermal insulation materials for support and ultra-lightness.
[0072] Example 4
[0073] 20 mL of tetraethyl silicate, 10.235 mL of anhydrous ethanol, 3.865 mL of ultrapure water and 0.1 mL of hydrochloric acid with a mass concentration of 10% were mixed, the mixture was stirred at a speed of 250 r / min, heated and evaporated at 80°C for 45 minutes to perform a hydrolysis reaction until the mass loss fraction of the spinning solution reached 58%. Then it was cooled to room temperature, the spinning solution was placed in a 15 mL syringe, and electrostatic spinning was performed when the solution dripped at a speed of 1 to 2 drops per second to obtain a SiO2 nanofiber membrane.
[0074] The parameters for electrospinning of the spinning solution are as follows: the inner diameter of the syringe needle is 0.41 mm, the outer diameter of the needle is 0.71 mm, the voltage of the electrospinning is 20 kV, the receiving device is coated with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 15 cm, the rotation speed of the receiving roller is 100 r / min, the translation speed of the electrospinning needle is 300 mm / min, the translation stroke of the electrospinning is 500 mm, the spinning temperature is 25 ° C, and the relative humidity is 35%.
[0075] 1 g of SiO2 nanofiber membrane was cut into pieces and added into 40 mL of DMF. The mixture was stirred at 1800 r / min for 1 h under a cantilever high-speed electric stirrer. During the stirring process, 1 g of PAN was added and the mixture was stirred at 2000 r / min for 20 min to form a uniform physically cross-linked PAN / SiO2 nanofiber colloid.
[0076] The PAN / SiO2 nanofiber colloid was added to ultrapure water and soaked for 72 hours. The water was changed 15 times during the soaking period. The intervals between water changes were the same. After the soaking, the colloid showed a certain shape to obtain PAN / SiO2 gel. The PAN / SiO2 gel with a certain shape was placed in a vacuum freeze dryer, frozen at -55°C for 12 hours, and then freeze-dried at -60°C and 5Pa for 72 hours to obtain PAN / SiO2 nanofiber aerogel.
[0077] The PAN / SiO2 nanofiber aerogel prepared with PAN as the matrix in this embodiment can achieve ultra-light performance. The PAN / SiO2 nanofiber aerogel with a thickness of 2 cm and a diameter of 3.6 cm does not produce obvious deformation when subjected to a pressure of more than 5 kg. At the same time, the measured mass of the PAN / SiO2 nanofiber aerogel is only 1.406 g, which can meet the requirements of thermal insulation materials for support and ultra-light properties.
[0078] The picture of C / SiO2 nanofiber aerogel prepared in Example 1 is as follows Figure 2 As shown, the picture of PAN / SiO2 nanofiber aerogel prepared in Example 4 is as follows Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the C / SiO2 nanofiber aerogel and PAN / SiO2 nanofiber aerogel of the present invention have ultra-light characteristics. The mass of the C / SiO2 nanofiber aerogel in Example 1 is only 0.904g, and the mass of the PAN / SiO2 nanofiber aerogel in Example 4 is only 1.406g, which can meet the demand for ultra-light characteristics of thermal insulation materials.
[0079] The compressive strength test of the C / SiO2 nanofiber aerogel prepared in Example 1 is shown in FIG. Figure 4 As shown in the figure, the compressive strength test of the C / SiO2 nanofiber aerogel prepared in Example 2 is as follows Figure 5 As shown by Figure 4 and Figure 5 It can be seen that the C / SiO2 nanofiber aerogel of the present invention has high compressive strength, and the strength can reach 170 kPa under the condition of 10% deformation, showing good mechanical properties.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing PAN / SiO2 nanofiber aerogel, characterized in that: The following steps are included: 1) mixing tetraethyl silicate and a solvent and evaporating the mixture to obtain a spinning solution, and electrospinning the spinning solution to obtain a SiO2 nanofiber membrane; 2) stirring and mixing SiO2 nanofiber membrane, polyacrylonitrile and N,N-dimethylformamide to obtain physically cross-linked PAN / SiO2 nanofiber colloid; 3) The PAN / SiO2 nanofiber colloid is immersed in water and then sequentially frozen and freeze-dried to obtain a PAN / SiO2 nanofiber aerogel.
2. The method for preparing PAN / SiO2 nanofiber aerogel according to claim 1, characterized in that: Step 1) The volume ratio of tetraethyl silicate to solvent is 1:0.6-1.1, the solvent is a mixture of anhydrous ethanol, water and hydrochloric acid, the volume ratio of anhydrous ethanol, water and hydrochloric acid is 95-115:30-45:1, and the mass concentration of hydrochloric acid is 5-15%.
3. The method for preparing PAN / SiO2 nanofiber aerogel according to claim 1 or 2, characterized in that: Step 1) The evaporation temperature is 78-85°C, the time is 35-100 min, and the evaporation is carried out under stirring conditions at a stirring rate of 150-450 r / min; During the electrostatic spinning process, the voltage is 15-30 kV, the temperature is 20-30° C., the relative humidity is 30-40%, and the distance between the spinning needle and the receiving roller is 10-25 cm.
4. The method for preparing PAN / SiO2 nanofiber aerogel according to claim 3, characterized in that: Step 2) The mass volume ratio of the SiO2 nanofiber membrane and N,N-dimethylformamide is 1g:35-50mL, and the mass volume ratio of polyacrylonitrile and N,N-dimethylformamide is 1g:30-60mL; the stirring and mixing time is 50-150min, and the rotation speed is 1600-2200r / min.
5. The method for preparing PAN / SiO2 nanofiber aerogel according to claim 4, characterized in that: Step 3) The soaking time is 72 to 120 hours, and the water is changed during the soaking period, and the number of times the water is changed is 10 to 20 times; The freezing temperature is -75 to -18°C, and the time is 12 to 36 hours; the freeze-drying pressure is 2 to 10 Pa, the temperature is -80 to -40°C, and the time is 65 to 110 hours.
6. PAN / SiO2 nanofiber aerogel prepared by the method for preparing PAN / SiO2 nanofiber aerogel according to any one of claims 1 to 5.
7. The method for preparing C / SiO2 nanofiber aerogel from PAN / SiO2 nanofiber aerogel according to claim 6, characterized in that: The following steps are included: The PAN / SiO2 nanofiber aerogel is pre-oxidized and carbonized in sequence to obtain C / SiO2 nanofiber aerogel.
8. The method according to claim 7, characterized in that The pre-oxidation temperature is 240-300°C, the time is 100-160 minutes, and the heating rate to the pre-oxidation temperature is 1-3°C / min; The carbonization temperature is 700-900° C., the time is 20-80 min, the heating rate to the carbonization temperature is 2-5° C. / min, and the carbonization is carried out under a nitrogen atmosphere.
9. C / SiO2 nanofiber aerogel prepared by the method for preparing C / SiO2 nanofiber aerogel by PAN / SiO2 nanofiber aerogel according to claim 7 or 8.
10. Use of the PAN / SiO2 nanofiber aerogel according to claim 6 or the C / SiO2 nanofiber aerogel according to claim 9 in thermal insulation materials.